Dzień lasu : Program uroczystości w Sopocie. (Gdynia : [s.n.], 1947)
Afisz z programem uroczystości, która miała miejsce 26.04.1947 r. w Sopocie.
Keywords: Sopot (Polska) -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- plakaty; Sopot (Polska) -- 1945-1970 -- źródła